2013
DOI: 10.1177/230949901302100219
|View full text |Cite
|
Sign up to set email alerts
|

Treating Giant Cell Tumours with Curettage, Electrocautery, Burring, Phenol Irrigation, and Cementation

Abstract: purpose. To report on 23 patients with giant cell tumour (GCT) of the femur or tibia treated with curettage, electrocautery, burring, phenol irrigation, and cementation. Methods. Records of these 14 men and 9 women aged 22 to 38 (mean, 31) years were reviewed. The most common site involved was the distal femur (n=13), followed by proximal tibia (n=8), proximal femur (n=1), and distal tibia (n=1). The lesions were classified as grade I (n=3), grade II (n=18), and grade III (n=2). Based on histology, the tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
0
26
0
4
Order By: Relevance
“…33, No. 5,2016 expanded outside the cortex because a safe surgical margin could not be achieved and the important neurovascular structures could not be protected. Cryotherapy can have effects deeper into the bone tissue; however, it is not used frequently enough due to its necrotic effect on the adjacent soft tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33, No. 5,2016 expanded outside the cortex because a safe surgical margin could not be achieved and the important neurovascular structures could not be protected. Cryotherapy can have effects deeper into the bone tissue; however, it is not used frequently enough due to its necrotic effect on the adjacent soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In surgical treatment, aggressive curettage is performed by preserving the cortical integrity to the greatest extent possible. Due to the high local recurrence only after the curettage, the use of local adjuvants was also reported such as phenol, liquid nitrogen, bone cement, hydrogen peroxide and alcohol (5,6). In GCT, the liquid nitrogen was first used by Marcove et al (6) as cryotherapy and reported to be an effective treatment.…”
mentioning
confidence: 99%
“…Adjunctive therapies, such as cryotherapy, electrocautery and/or instillation of chemicals such as phenol, alcohol or steroids, may be used to decrease recurrence rates, with varying success. 1,4,9,10 This does not usually change the post- (Fig. 1).…”
Section: Surgical Considerations and Techniquementioning
confidence: 89%
“…Current evidence indicates that curettage should be supplemented with a combination of chemical cautery, cryotherapy or electrical cautery followed by methylmethacrylate cement to limit recurrence. 20,21 In the instance of this case a combination of curettage, burring and cryotherapy was used, after which cement was inserted in the cavity. The distal humerus was then stabilised with a postero-medial plate.…”
Section: Discussionmentioning
confidence: 99%